Photobiomodulation therapy combined to static magnetic field before blood flow restriction training in healthy individuals: protocol for a double-blind, randomized, placebo-controlled trial - Ferlito, João Vitor; Leal-Junior, Ernersto Cesar Pinto; Salvador, Mirian; De Marchi, Thiago (Manual Therapy, Posturology & Rehabilitation Journal, 2021)
Background: Photobiomodulation therapy with static magnetic field (PBMT/sMF) stands out for being a non-pharmacological resource with bioenergetic effects capable of accelerating muscle recovery, delaying muscle fatigue and potentiate gains in different training protocols. In recent years, blood flow restriction (BFR) associated with low load exercise (20-30% 1RM/MVC) has demonstrated positive effects on muscle performance. However, the effects of PBMT/sMF combined with BFR training are still unknown. Objective: Verify the effects of PBMT/sMF associated with BFR training and compared with high load training (HLT) in the muscle strenght, muscle damage, inflammation, and the oxidative stress. Materials and methods: This are a protocol of a randomized, double-blind, placebo-controlled clinical trial. The participants will be healthy men between the ages of 18 to 40 years, with no practice in upper limb strength training in the previous three months. The voluntaries will be randomly divided into four groups: (1) PBMT/sMF + BFR ; (2) PBMT/sMF + HLT; (3) placebo + BFR; (4) placebo + HLT. The PBMT/sMF will be applied immediately before strengthening protocol (4 sets x 20 repetitions of elbow flexion). The BFR groups will undergo to exercise with low load (30% of MVC), while the HLT groups will performed the same protocol with 80 % of MVC. The primary outcome will be muscle strength, measured in baseline, fourth, eighth week of training and detraining period. The secondary outcomes include measured the fatigue resistance, arm circumference, muscle damage, inflammatory and oxidative stress levels in one session, during, after intervention and detraining. Discuss: This trial will elucidate the effects of PBMT/sMF combined with BFR training and compared with HLT.